Creating Collaborative Learning Spaces (Makerspaces) as Impetus for Sustainable Change in Nigeria Federal Polytechnic and Monotechnic Libraries - Sokoya, Abiola Abosede; Alabi, Adefunke Olanike (POMLIF Journal of Library and Information Science, 2018)
Creating Collaborative Learning Spaces (Makerspaces) as Impetus for Sustainable Change in Nigeria Federal Polytechnic and Monotechnic Libraries